(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study focused on the reintegration of workers into the Brazilian IT workforce after the pandemic, specifically examining the literature on the subject. When individuals in the Brazilian IT industry return to work, their psychological well-being (PWB) is impacted. Findings revealed a preference for teleworking, showing advantages and disadvantages for companies. For example, increasing productivity gains for workers, including working from anywhere without geographical restrictions and reporting better work/work-life balance, are disclosed.